Diagnostic Utility of INSM1 in Medullary Thyroid Carcinoma. (September 2021) - Seok, Jae Yeon; Kang, Myunghee; De Peralta-Venturina, Mariza; Fan, Xuemo
Insulinoma-associated protein 1 (INSM1) is shown to be an excellent marker for neuroendocrine differentiation. However, the diagnostic utility of INSM1 in medullary thyroid carcinoma (MTC) has not yet been extensively investigated. INSM1 staining was performed on 21 MTCs, 7 MTC mimickers (including 3 papillary carcinomas, 2 poorly differentiated carcinomas, 1 follicular adenoma, and 1 nodular plasma cell hyperplasia), and 3 cases of C-cell hyperplasia. INSM1 staining of these cases was compared with the traditional MTC markers including calcitonin (CT), monoclonal carcinoembryonic antigen (mCEA), chromogranin A (CgA), and synaptophysin (Syn). The H -score was generated using the QuPath program, an open-source image analysis software. All 21 MTC cases and 3 C-cell hyperplasia cases were positive for all markers. The MTC mimickers were entirely negative for INSM1. INSM1 and Syn displayed, more consistently, high expression with minimal variability than CgA that showed a wide range of expression with significant variability. mCEA and CT exhibited mostly a high expression with some variability. Being a nuclear stain, interpretation was easier with INSM1 compared to other cytoplasmic markers. INSM1 is an excellent marker for neuroendocrine differentiation, entirely applicable in the diagnosis of MTC and C-cell hyperplasia with high sensitivity and specificity. In comparison with the traditional MTC markers, INSM1 is unique in the crisp nuclear staining pattern with a consistent, diffuse, and strong expression. INSM1 can be potentially combined with CT or mCEA as a dual stain, especially when the lesional tissue is limited for a panel of immunostains.